More than the Sum of Its Parts: Donor-Sponsored Cash-for-Work Programmes and Social Cohesion in Jordanian Communities Hosting Syrian Refugees - Tina Zintl; Markus Loewe (The European Journal of Development Research, 2022)
Cash-for-Work (CfW)/public works programmes have gained great interest recently because they can deliver employment and income for vulnerable households, in addition to dearly needed infrastructure. Studying donor-funded CfW programmes for Syrian refugees and their local neighbours in Jordan we show that CfW can also improve social cohesion, which is particularly important in the context of state fragility and migration. The studied programmes strengthen the sense of belonging and horizontal trust of participants and non-participants, refugees and locals, and in particular women. Their effect on vertical trust, however, is more ambiguous because many Syrians and Jordanians attribute positive effects to donor support rather than to Jordanian authorities. We use a mixed method approach including semi-structured interviews with 390 CfW participants, other community members and neutral observers and a quantitative analysis of a survey covering all 1847 participants of one CfW programme.
Keywords: A13; D02; D63; F22; H31; H53; H75; I38; F15; J16; 330; Refugees; Cash-for-work; Public works; Social cohesion; Social protection; Jordan; Middle East and North Africa (MENA); Social transfer schemes